2014
DOI: 10.1267/ahc.13040
|View full text |Cite
|
Sign up to set email alerts
|

ABCC11/MRP8 Expression in the Gastrointestinal Tract and a Novel Role for Pepsinogen Secretion

Abstract: ATP-binding cassette (ABC) transporters are involved in chemotherapy resistance. Multidrug-resistance protein 8 (ABCC11/MRP8) is also involved in 5-fluorouracil (5-FU) metabolism. 5-FU and its derivatives are widely used in the treatment of gastrointestinal tract cancers, but little is known about the contribution of ABCC11/MRP8 to gastrointestinal tract and related cancers. Here, we report our investigation of ABCC11/MRP8 expression in normal and cancerous gastrointestinal tract tissues and reveal its novel r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Primary antibody binding was detected using Alexa Fluor 488 conjugated goat anti-rabbit IgG (Life technologies, USA, 1:1000) and Alexa Fluor 680 conjugated goat anti-mouse IgG (Life technologies, USA, 1:1000) secondary antibodies [27]. The cells were mounted and counterstained with DAPI (4,6-diamidino-2-phenylindole, dihydrochloride, 300 μgmL) (Molecular Probes, USA) for nuclear staining [28]. Fluorescence images were captured with a confocal laser scanning microscope (A1, NIKON InSTECH, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Primary antibody binding was detected using Alexa Fluor 488 conjugated goat anti-rabbit IgG (Life technologies, USA, 1:1000) and Alexa Fluor 680 conjugated goat anti-mouse IgG (Life technologies, USA, 1:1000) secondary antibodies [27]. The cells were mounted and counterstained with DAPI (4,6-diamidino-2-phenylindole, dihydrochloride, 300 μgmL) (Molecular Probes, USA) for nuclear staining [28]. Fluorescence images were captured with a confocal laser scanning microscope (A1, NIKON InSTECH, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…ABCC11 (MRP8) is found in brain, breasts, lungs, liver, kidney, placenta, prostate, testes, and apocrine glands, as well as in cancerous tissues (Kruh et al, 2007 ). Its substrates are lipophilic anions, as well as cyclic nucleotides and anticancer drugs (Bortfeld et al, 2006 ; Matsumoto et al, 2014 ). ABCC1, ABCC11, and ABCG2 transport E1-S, while ABCC1, ABCC4, ABCC11, and ABCG2 mediate excretion of DHEA-S (Table 2 ).…”
Section: Intracrine Actions Of Steroid Hormonesmentioning
confidence: 99%
“…However, the effect of MRP8 genotypes on breast cancer is likely to be more complex since there are studies showing that the association could not be observed in Caucasian (82). Although there is a report showing a decrease in MRP8 level in breast cancer (83), high level of MRP8 was reported in breast cancer and gastric cancer cell lines by other groups (84,85). Other substrates of MRP8 include MTX (79), 5-FU, and pemetrexed (86,87).…”
Section: Mrp8mentioning
confidence: 99%